Molecular and clinical characteristics of ATP1A3-related diseases - Li, Yinchao; Liu, Xianyue; Wang, Chengzhe; Su, Zhengwei; Zhao, Ke; Yang, Man; Chen, Shuda; Zhou, Liemin (Frontiers in Neurology, 2022)
Objective With the in-depth study of ATP1A3 gene-related diseases, the phenotypic spectrum of the ATP1A3 gene has been further expanded. By analyzing the clinical features and phenotypes of ATP1A3 gene-related diseases and exploring the distribution patterns of mutations in sub-regions of ATP1A3 protein, we aimed to potentially identify the mechanisms by which the ATP1A3 gene causes neurological dysfunction, thus providing new and effective therapeutic approaches. Methods By searching and screening PubMed, OMIM, and HGMD databases for case reports of ATP1A3 gene-related diseases, we collected clinical information and genetic testing results of patients and reviewed and analyzed the disease characteristics on the clinical phenotype spectrum associated with mutations, genetic characteristics of mutations, and effects of drug therapy. Results We collected 902 clinical cases related to the pathogenesis of the ATP1A3 gene. From the results of previous studies, we further clarified the clinical characteristics of diseases related to the ATP1A3 gene, such as AHC, RDP, CAPOS, and RECA; frequency of mutations in different phenotypes and their distribution in gene and protein structure; and differences in mutations in different clinical phenotypes. In terms of the efficacy of drug treatment, 80 of the 124 patients with AHC were treated with flunarizine, with an effective rate of about 64.5%. Conclusion The nervous system dysfunction caused by the ATP1A3 gene mutations was characterized by a group of genotypic–phenotypic interrelated disease pedigrees with multiple clinical manifestations. The results of this study may help guide the diagnosis and treatment of ATP1A3 gene-related diseases and provide new ideas for further exploring the mechanisms of nervous system diseases due to ATP1A3 gene mutations.